Possible risk for cancer among children born following assisted reproductive technology in Israel. Issue 4 (17th October 2016) - Lerner‐Geva, Liat; Boyko, Valentina; Ehrlich, Shelley; Mashiach, Shlomo; Hourvitz, Ariel; Haas, Jigal; Margalioth, Ehud; Levran, David; Calderon, Ilan; Orvieto, Raoul; Ellenbogen, Adrian; Meyerovitch, Joseph; et al.
Abstract: Background: Among children conceived by assisted reproductive technology (ART), increased risk of adverse birth outcomes has been observed, including multiple births, preterm births, and congenital malformations. Regarding cancer among ART‐conceived children, findings are discrepant. Methods: This is a historical cohort of 9, 042 ART‐conceived children and 211, 763 spontaneously conceived (SC) children born from 1997 through 2004. The median duration of follow‐up was 10.6 years (interquartile range 9.0–12.3) in the ART group and 9.3 years (interquartile range 8.0–10.6) in the SC group. The cohort database was linked with the Israel National Cancer Registry updated until December 31, 2011 using each child's personal identification number. Results: Twenty‐one cases of cancer were identified in the ART group (2.2 per 10, 000 person‐years), as compared to 361 cancer cases in the SC group (1.8 per 10, 000 person‐years). The relative risk (RR) for overall cancer in the ART group compared to the SC group adjusted for maternal characteristics was 1.18 (95% confidence interval [CI] 0.80–1.75). ART children had a significantly increased risk for specific cancers, although based on small number of cases, including two cases of retinoblastoma (RR 6.18, 95% CI 1.22–31.2), as well as four cases of renal tumors (RR 3.25, 95% CI 1.67–6.32). Conclusion: A statistically significant increased risk for two pediatric cancers was found. However, for overall types of cancer the risk estimate was elevated but not statistically significant. Further studies with larger sample size and longer follow‐up time are warranted in order to either confirm or refute these findings.